PENGARUH PEMBERIAN JAHE MERAH TERHADAP GANGGUAN PERNAPASAN PASIEN ISPA PADA BALITA DI PUSKESMAS PAYUNG SEKAKI - Linda Suryani; Siti Zakiah Zulfa (STIKes Al-Insyirah Pekanbaru, 2022)
Acute Respiratory Infection (ARI) is an acute infectious disease that attacks the upper respiratory tract and lower respiratory tract. ARI can cause mild symptoms such as cough and runny nose, moderate symptoms such as shortness of breath and severe symptoms. ARI can attack children if the body's resistance (immunology) decreases. One of the non-pharmacological therapies to reduce the symptoms of ARI is red ginger which contains chemical compounds of flavonoids, alkaloids and essential oils. The red ginger plant was found to be highly effective against periodontitis respiratory syncytial virus infections. This research is a quantitative research, quasi-experimental design with a non-equivalent control group pre-test and post-test approach. This research was conducted in June - September 2022 at Payung Sekaki Health Center Pekanbaru. The study population was Toddlers Suffering from ARI at the Payung Sekaki Health Center in June – August totaling 98 people, a sample of 30 people for each control and intervention group. Sampling using purposive sampling technique. The research instrument used was a questionnaire sheet, and red ginger boiled water. Data analysis used univariate and bivariate data analysis using independent t-test and paired t-test. The results of the study showed that respiratory disorders in ARI patients before and after being given intervention by taking standard health care medicine plus red ginger boiled water with 30 respondents obtained an average pre-intervention (pre-test) of 61.49 with a standard deviation of 20.046 while the average after the intervention ( post test) 38.51 with a standard deviation of 15.033. The results of the study using the paired t test showed that for the experimental group after being given red ginger boiled water and standard therapy at the puskesmas with 30 respondents, the mean was 45.809 with a P-value of 0.025 (<0.05). It can be concluded that there is an effect of giving red ginger plus standard therapy at the puskesmas by consuming only standard therapy at the puskesmas. It is hoped that at the Payung Sekaki Health Center this research can be used as a source of knowledge for the local community and can be used as a complementary therapy guideline to reduce the symptoms of ARI.